STRATEGI PEMERINTAH DAERAH DALAM PENGEMBANGAN BADAN USAHA MILIK DESA DI KABUPATEN ROKAN HULU TAHUN 2012-2014 ( Studi : BUM Desa Mitra Usaha Mulya Dan BUM Desa Langkitin Di Kecamatan Rambah Samo ) - Rio Halomoan; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Government Regulation No. 72 Year 2005 tentangDesa: Article 78, namely: To improve people's income and the Village, the Village Government can establish village-owned enterprises in accordance with the needs and potential of the village. Provincial and District Government support is quite large, in the formation of BUM village is referring to the rule area Rokan Hulu No. 8 of 2007 on village-owned enterprises and implemented by decree Rokan Hulu No. 18 of 2009 and replaced by decree No. 64 2014 on the implementation guidelines village-owned enterprises.The method used in this study is a qualitative research with descriptive approach, with a focus on: (1) Strategy Regional Government in the development of village-owned enterprises (2) factors that support the development BUM Village Business Partner Mulya (3) Factors hindering the development of BUM Village Langkitin ,Results of the study is that the strategy of local governments in the development of village-owned enterprises to establish district coordinator as a builder BUM village in Rokan Hulu a factor supporting the development BUM village in Rokan Hulu one BUM village Mulya Business Partners. But would not all BUM village is managed and run in accordance with the purpose of BUM village was myself, One Village BUM Langkitin. So it can be said BUM Langkitin village is only limited nameplate Village BUM, BUM and activity of village Not Running.Keywords: Strategy, Development, Village-owned enterprises.